Peningkatan Keterampilan Menulis Teks Narasi Dengan Model Cooperative Tipe Think Talk Write di Kelas IV SD Negeri 18 Air Tawar Selatan Kota Padang - Putri, Elga Dewi; Suriani, Ari (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe how to improve students' writing skills in Indonesian learning using the Think Talk Write (TTW) type cooperative model in grade IV of SDN 18 Air Fresh, South Padang City. This type of research is classroom action research using qualitative and quantitative approaches. This research was carried out in two cycles, with the research procedure consisting of planning, implementation, observation, and reflection. Data collection techniques are in the form of observation or observation analysis, tests and non-tests. The subjects of this study are classroom teachers as observers, researchers as practitioners or teachers, and grade IV students of SDN 18 Air Tawar Selatan Padang City totaling 17 people. The results of the study showed that the teaching module of the first cycle was obtained on average 87.45%, increasing in the second cycle to 95.83%. The results of the implementation of teacher aspect learning in the first cycle of teacher activities averaged 85.4%, increasing in the second cycle to 95.83%. The implementation of the first cycle in student activities averaged 85.4%, increasing in the second cycle of 95.83%. The learning outcomes of the first cycle of knowledge with an average of 72.94% of students and the second cycle with an average of 88.64% of students. The results of the skill assessment in the first cycle averaged 75.97%, then increased in the second cycle of 87.41%. Based on these results, it can be concluded that the Think Talk Write type cooperative model can improve the writing skills of grade IV elementary school students.